Channelling His Inner Semiramis: Alexander and His Quest to Overcome the Assyrian Queen - Pruša, Libor (Sapiens ubique civis, 2023)
Alexander the Great desired to outdo all the great generals in history and one of them was the famed Queen Semiramis. The episodes from their lives were occasionally put in comparison, and both gained legendary status among the ancient rulers. Alexander eventually surpassed Semiramis, but why was she so important to Alexander? The life of Semiramis was for the first time described by Ctesias in his Persica. The problem is that he died several decades before the rule of Alexander. Therefore, he did not record the striking similarities between her life and the episodes from Alexander’s conquest. Ctesias’ original account was adapted by later authors who altered some elements of the story in the wake of Alexander’s expedition. In this article, we will focus on the similarities in the episodes from the lives of two conquerors, how Alexander fared compared to the Assyrian queen, and who was responsible for putting the tales in comparison, whether it was Ctesias, Diodorus, or someone else.